2005
DOI: 10.7589/0090-3558-41.3.473
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Dynamics of Sin Nombre Viral Rna and Antibody in Deer Mice in Montana

Abstract: Infections with hantaviruses in the natural host rodent may result in persistent, asymptomatic infections involving shedding of virus into the environment. Laboratory studies have partially characterized the acute and persistent infection by Sin Nombre virus (SNV) in its natural host, the deer mouse (Peromyscus maniculatus). However, these studies have posed questions that may best be addressed using longitudinal studies involving sequential sampling of individual wild-caught, naturally infected mice. Using en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
53
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 22 publications
7
53
0
1
Order By: Relevance
“…Botten et al reported an initial peak in SNV RNA levels in lung samples at 21 days PI, followed by a second peak at 60 days PI (15). In another report on SNV, Kuenzi et al found a variation in PCR positivity of blood samples from wild-caught deer mice (16). These authors suggested 2 interpretations of the results: either that viral RNA is consistently present in the blood but is near the limits of PCR detectability or viral RNA reappears in blood as a consequence of unknown physiologic events.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Botten et al reported an initial peak in SNV RNA levels in lung samples at 21 days PI, followed by a second peak at 60 days PI (15). In another report on SNV, Kuenzi et al found a variation in PCR positivity of blood samples from wild-caught deer mice (16). These authors suggested 2 interpretations of the results: either that viral RNA is consistently present in the blood but is near the limits of PCR detectability or viral RNA reappears in blood as a consequence of unknown physiologic events.…”
Section: Discussionmentioning
confidence: 94%
“…Animals were sampled for saliva, urine, and feces on days 0, 1, 2, 3,4,8,9,11,14,16,21,28,35,42,49,56,63,70,77,84,91, and 133 PI. Serum samples were obtained on day 21 and at the termination of the experiment (day 133 PI).…”
Section: Subcutaneous Inoculation and Sample Handlingmentioning
confidence: 99%
“…Also, studies are warranted to ascertain if the persistence of MJNV in Ussuri shrews results from heightened regulatory T-cell responses, as described previously for SEOV-infected male Norway rats (17,18). Chronic hantavirus infection in rodents is usually characterized by alternating positivity and negativity for hantavirus RNA, instead of strict concordance between the presence of detectable anti-hantavirus antibody and that of hantavirus RNA (30). Similarly, in this study, the detection of anti-MJNV IgG antibodies in the absence of detectable MJNV RNA may be attributed either to the insensitivity of the RT-PCR analysis or fluctuating viral loads in tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Periods of increased contact rates between deer mice, such as during the onset of breeding activities in the spring, may be correlated with recent infections (Kuenzi et al, 2005). A greater proportion of recent SNV infections were recorded in spring versus fall for deer mice in Alberta, Canada (Safronetz et al, 2006).…”
Section: Introductionmentioning
confidence: 99%